CHARACTER AND CHARACTERIZATION IN THE FILM INSIDE OUT BY PETER HANS DOCTOR - Hendarsyah, Jelita Dewanty (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2020)
In the animated film Inside Out explained about various types of emotions, including five basic emotional characters found in the film Inside Out, such as Joy (happy), Sadness (sad), Anger (angry), Fear (fear) and Disgust (disgust or hate). The basic emotions in this animated film will be interpreted by the signs implicit in the film. Mass media are official means and channels as a communication tool to spread news and messages to the wider community. But the media are not only a source of information and entertainment, but are also used as a means of communication. This study aims to find out how to present basic human emotions in the animated film Inside Out. The method used in this research Semiotic analysis method is Roland Barthes's semiotic analysis, by looking at the meaning of Denotation, Connotation, and Myth. The result we can see from the specified criteria, namely physical, fashion and clothing. This research shows that there are denotations, connotations, and myths in the representation of basic emotions in the film Inside Out.